Dual-wavelength q-switched fiber laser generation by incorporating 2D materials in D-SMS fiber structure - Zaini, Muhammad Aizat Zaim; Md Saaid, Nur Farzana Fasihah; Mohd Rusdi, Muhammad Farid; Abdul Latiff, Anas; Ab Rahman, Mohd Fauzi; Al-Masoodi, Ahmed Hasan Hamood (2023)
We demonstrate a dual-wavelength Q-switched fiber laser generation by inserting a